Equine cryptosporidiosis - Inácio, Sandra Valéria [UNESP]; De Aquino, Monally Conceição Costa [UNESP]; Do Amaral, Anaiza Simão Zucatto; Prando, Luciana [UNESP]; Oliveira, Bruno César Miranda [UNESP]; Fukumori, Felipe Yoshio [UNESP]; Suzuki, Celso Tetsuo Nagase; Gomes, Jancarlo Ferreira (My University, 2017)
In immunocompetent individuals cryptosporidiosis is a self-limiting disease, but in young and immunocompromised can even be lethal, and until now there is no treatment considered effective. Diarrhea is one of the symptoms which may occur in infected horses and was detected in intermittently or chronic forms associated with weight loss, inappetence and lethargy. This animal species is usually infected by Cryptosporidium parvum, Cryptosporidium genotype horse and a more recent report by Cryptosporidium hominis. Data on the molecular epidemiology to investigate the zoonotic potential of infection by this parasite in horses are still scarce. Public health policies restrict access horses in watershed areas, presenting a negative factor in relation to the use of these animals as a recreational activity at these places. Therefore, studies related to this disease are very important, considering their zoonotic potential and the lack of information about environmental contamination with Cryptosporidium oocysts released by horses.
Keywords: Cryptosporidiosis; Molecular biology; Protozoa